Activity based restorative therapy considerations for children: medical and therapeutic perspectives for the pediatric population - Reeves, Brooke; Smith, Emily; Broussard, Miranda; Martin, Rebecca (Frontiers in Rehabilitation Sciences, 2023)
Well-established scientific evidence demonstrates that activity is essential for the development and repair of the central nervous system, yet traditional rehabilitation approaches target muscles only above the lesion as a means of compensation. Activity-Based Rehabilitation (ABR) represents an evolving paradigm shift in neurorehabilitation targeting activation of the neuromuscular system below the lesion. Based on activity-dependent plasticity, ABR offers high intensity activation of the nervous system to optimize the capacity for recovery, while working to offset the chronic complications that occur as a result of neurologic injury. Treatment focus shifts from compensatory training to promotion of restoration of function with special emphasis on normalizing sensory cues and movement kinematics. ABR in children carries special considerations for a developing nervous system and the focus is not just restoring functions but advancing functions in line with typical development. Application of activity-based interventions includes traditional rehabilitation strategies at higher intensity and frequency than in traditional models, including locomotor training, functional electrical stimulation, massed practice, and task specific training, applied across the continuum of care from early intervention to the chronic condition.